Biomarkers of the Physical Function Mobility Domains Among Patients Hospitalized in Internal Medicine - Vrbová, P; Valášková, S; Gažová, A; Smaha, J; Kužma, M; Kyselovič, J; Payer, J; Koller, T (Physiological research, 2021)
Hospitalized patients in internal medicine have an increased risk of low physical reserve which further declines during the hospital stay. The diagnosis requires bed-side testing of functional domains or more complex investigations of the muscle mass. Clinically useful biomarkers of functional status are needed, thus we aimed to explore the potential of microRNAs. Among hospitalized patients, we recorded the basic demographics, anthropometrics, nutritional status, and physical function domains: hand-grip strength (HGS, abnormal values M<30 kg, W<20 kg), balance (<30 s), chair-stands speed (CHSS<0.5/s) and gait speed (GS<0.8 m/s). A panel of five micro-RNAs (miRNA 1, miRNA 133a, miRNA 133b, miRNA 29a, miRNA 29b) and basic blood biochemistry and vitamin D values were recorded. We enrolled 80 patients (M40, W40), with a mean age of 68.8±8.4 years. Obesity was observed in 27.5 % and 30 %, low HGS and low CHSS in 65.0, 77.5 %, and 80, 90 % of men and women respectively. The median hospital stay was 6.5 days. MiRNA29a and miRNA29b have the strongest correlation with the triceps skinfold (miRNA 29b, r=0.377, p=0.0006) and CHSS (miRNA 29a, r=0.262, p=0.02). MiRNA 29a, miRNA 29b and 133a levels were significantly higher in patients with CHSS<0.5/s. Other anthropometric parameters, mobility domains, or vitamin D did not correlate. All miRNAs except of miRNA 1, could predict low CHSS (miRNA29b, AUROC=0.736 CI 0.56-0.91, p=0.01), particularly in patients with low HGS (miRNA 29b, AUROC=0.928 CI 0.83-0.98). Among hospitalized patients in internal medicine, low functional status was frequent. MicroRNAs were fair biomarkers of the antigravity domain, but not other domains. Larger studies with clinical endpoints are needed.
Keywords: Humans; lidé středního věku; MicroRNAs; kohortové studie; Female; Aged; dospělí; vnitřní lékařství; tělesná výkonnost; senioři; lidé; Biomarkers; Cohort Studies; fyzikální vyšetření; Adult; biologické markery; ženské pohlaví; Inpatients; Male; Middle Aged; Physical Examination; hospitalizovaní pacienti; Internal Medicine; mikro RNA; mužské pohlaví; Physical Fitness